2022
DOI: 10.3390/ijms231912044
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Urinary Biomarkers for Assessing Bladder Condition and Histopathology in Patients with Interstitial Cystitis/Bladder Pain Syndrome

Abstract: This study investigated the usefulness of urinary biomarkers for assessing bladder condition and histopathology in patients with interstitial cystitis/bladder pain syndrome (IC/BPS). We retrospectively enrolled 315 patients (267 women and 48 men) diagnosed with IC/BPS and 30 controls. Data on clinical and urodynamic characteristics (visual analog scale (VAS) score and bladder capacity) and cystoscopic hydrodistention findings (Hunner’s lesion, glomerulation grade, and maximal bladder capacity (MBC)) were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…We also demonstrated increased expression of inflammatory mediators in the urinary bladder including neurotrophic factors (e.g., NGF, BDNF), chemokines (CXC) and IL-6 expression in the urinary bladder consistent with a large body of literature demonstrating roles for inflammatory mediators in preclinical animal models of and in IC/BPS patients (18,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Urinary bladder neurotrophic factor (i.e., NGF, BDNF), CXCL9, CXCL10 and IL-6 expression was increased in mice with CYP alone, RVS alone and CYP+RVS compared to control mice.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We also demonstrated increased expression of inflammatory mediators in the urinary bladder including neurotrophic factors (e.g., NGF, BDNF), chemokines (CXC) and IL-6 expression in the urinary bladder consistent with a large body of literature demonstrating roles for inflammatory mediators in preclinical animal models of and in IC/BPS patients (18,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Urinary bladder neurotrophic factor (i.e., NGF, BDNF), CXCL9, CXCL10 and IL-6 expression was increased in mice with CYP alone, RVS alone and CYP+RVS compared to control mice.…”
Section: Discussionsupporting
confidence: 83%
“…In this paper, we describe our characterization of the SISE model including, bladder function with conscious, open outlet continuous cystometry and somatic sensitivity with von Frey filament testing. We have also examined corticosterone expression, and expression of inflammatory mediators including neurotrophic factor (NGF, BDNF) (18)(19)(20), chemokine (CXC) and interleukin-6 (IL-6) (18,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) expression in the urinary bladder. These initial results demonstrated that CYP alone, or RVS alone creates a change in the inflammatory environment of the urinary bladder and a systemic increase in corticosterone expression but does not result in a change in bladder function or somatic sensitivity until CYP is combined with RVS (CYP+RVS).…”
Section: Introductionmentioning
confidence: 99%
“…The urinary oxidative stress biomarkers 8-OHdG and 8-isoprostane also showed a high diagnostic ability to distinguish the European Society for the Study of Interstitial Cystitis (ESSIC) type 2 IC/BPS patients from controls [ 20 ]. These urinary biomarker levels are likely to reflect the bladder inflammatory condition rather than the underlying histopathological status in patients with IC/BPS [ 28 ]. Urinary cytokine profiles are different between patients with ESSIC type 2 IC/BPS and OAB [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 Urinary biomarkers are the most explored and may be used as tools to distinguish IC/BPS from other bladder diseases. 7,8 To our knowledge, no study has been conducted on blood biomarkers in humans. Therefore, we initiated clinical studies on blood biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Although stool and bladder tissue have been investigated as potential sources of biomarkers, no universal biomarkers have been identified for clinical diagnosis 6 . Urinary biomarkers are the most explored and may be used as tools to distinguish IC/BPS from other bladder diseases 7,8 . To our knowledge, no study has been conducted on blood biomarkers in humans.…”
Section: Introductionmentioning
confidence: 99%